2018
DOI: 10.1186/s12864-018-5043-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis reveals key genetic factors associated with probiotic property in Enterococcus faecium strains

Abstract: BackgroundEnterococcus faecium though commensal in the human gut, few strains provide a beneficial effect to humans as probiotics while few are responsible for the nosocomial infection. Comparative genomics of E. faecium can decipher the genomic differences responsible for probiotic, pathogenic and non-pathogenic properties. In this study, we compared E. faecium strain 17OM39 with a marketed probiotic, non-pathogenic non-probiotic (NPNP) and pathogenic strains.ResultsE. faecium 17OM39 was found to be closely r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 113 publications
6
38
1
Order By: Relevance
“…The minute influence on the size of core genes with the addition of genomes indicated that the analyzed E. cecorum genomes were sufficient to construct the representative core-genome. The results were in agreement with previous studies of E. faecalis [ 53 , 54 ]. The small pan-genome size and inclusion of 43% gene families in core genes in the clinical isolates showed their conserved nature.…”
Section: Discussionsupporting
confidence: 93%
“…The minute influence on the size of core genes with the addition of genomes indicated that the analyzed E. cecorum genomes were sufficient to construct the representative core-genome. The results were in agreement with previous studies of E. faecalis [ 53 , 54 ]. The small pan-genome size and inclusion of 43% gene families in core genes in the clinical isolates showed their conserved nature.…”
Section: Discussionsupporting
confidence: 93%
“…The pan-genome contained a family of 3,915 genes, of which 1,959 genes were conserved across strains (Figures 2D,E). As the number of comparative strains increased, the size of the pan genome gradually increased, while the size of the core genome stabilized similar to the previous study of the E. faecium (Mikalsen et al, 2015;Ghattargi et al, 2018). Based on this result, we found an open pan-genome structure in 10 adjacent E. faecium strains including BIOPOP-3.…”
Section: Discussionsupporting
confidence: 87%
“…These direct threshold methods ensure that sequences that are more dissimilar than the threshold do not appear in the same cluster, and are extremely fast. CD-HIT has been used for pan-genome clustering for different microbial species (3,8,9), while UCLUST is the default clustering algorithm in the Bacterial Pan Genome Analysis tool (BPGA) (10), which is also used for multiple species’ pan-genome analysis (1115). Importantly, when using direct-threshold methods , the correct value of the threshold may be difficult or impossible to determine, and an incorrectly chosen threshold value directly impacts clustering accuracy.…”
Section: Introductionmentioning
confidence: 99%